INSULIN THERAPY IN NWFP PAKISTAN - AHMAD, MAHMUD (Journal of Ayub Medical College Abbottabad, 2001)
The management of Type I and Type II Diabetes Mellitus has improved because of tremendous improvement in Insulins over the years, but unfortunately majority of patients in our country cannot afford these, especially the human insulin, and are deprived of the benefits. Access to insulin should be regular and uninterrupted. Insulin therapy has changed the outlook of Type I - IDDM from certain death to almost normal existence. The discovery of Banting and Best in 1921, was the greatest breakthrough in this field. Since then continuous improvement in Insulins is taking place. In I980Recombinant DNA origin insulin came into use. These insulins are less antigenic, purer, better absorbed and lesser doses are required as compared to animal origin insulins. Human Insulin was first product of biotechnology to enter the clinical Arena2. By 1950 exact structure of insulin molecule was known3. In developed countries the prognosis of Diabetes has dramatically improved over last twenty years with life expectancy approaching towards normal, especially in Denmark4.